2019
DOI: 10.1093/jac/dkz242
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to critically important antimicrobials in Australian silver gulls (Chroicocephalus novaehollandiae) and evidence of anthropogenic origins

Abstract: Objectives Antimicrobial resistance (AMR) to critically important antimicrobials (CIAs) amongst Gram-negative bacteria can feasibly be transferred amongst wildlife, humans and domestic animals. This study investigated the ecology, epidemiology and origins of CIA-resistant Escherichia coli carried by Australian silver gulls (Chroicocephalus novaehollandiae), a gregarious avian wildlife species that is a common inhabitant of coastal areas with high levels of human contact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 42 publications
6
80
0
Order By: Relevance
“…Because the mcr-1 gene is typically located on mobile genetic elements, it may be transferred among bacteria through horizontal gene transfer 4 ; some bacterial infections could become difficult or impossible to treat if colistin resistance spreads to bacteria resistant to other antimicrobials 5 . Since 2015, mcr-1 has been detected in at least 31 countries on six continents, including in the U.S. 5,6 , where it has been detected in human and domestic swine isolates from 21 states 7 .…”
Section: Days Because Gulls Are Mobile and Can Shed Antimicrobial-rementioning
confidence: 99%
“…Because the mcr-1 gene is typically located on mobile genetic elements, it may be transferred among bacteria through horizontal gene transfer 4 ; some bacterial infections could become difficult or impossible to treat if colistin resistance spreads to bacteria resistant to other antimicrobials 5 . Since 2015, mcr-1 has been detected in at least 31 countries on six continents, including in the U.S. 5,6 , where it has been detected in human and domestic swine isolates from 21 states 7 .…”
Section: Days Because Gulls Are Mobile and Can Shed Antimicrobial-rementioning
confidence: 99%
“…The role of resident ARGs in commensal bacteria in the development and transmission of resistance is not fully understood. Transmission of ARGs need to be considered beyond interactions amongst humans, as recent evidence indicates that wildlife and domestic animals act as ‘ecological sponges’ of ARGs . A number of resistance strains have been identified in diverse animal populations from companion animals, livestock, to wild boar and seagulls.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Genome sequencing has revealed that strains belonging to human‐associated pathogenic clones, such as Escherichia coli , have been found in Australian silver gulls. Further study is required to understand the effects of dissemination of ARGs of these animal populations, particularly those that can travel significant distances …”
Section: Antibiotic Resistancementioning
confidence: 99%
See 2 more Smart Citations